Analisis Kebijakan Pemerintah Dalam Menangani Tindak Pidana Penyalahgunaan Narkotika Di Kalangan Remaja - Ahmad Aridho; Denada Damanik; Reh Bungana; Maulana Ibrahim (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
This research aims to examine (1) the reality of criminal acts of narcotics abuse in Indonesia, (2) what government policies are in controlling narcotics abuse against teenagers. This research uses qualitative research with bibliometric analysis methods, Google Scholar Publish or Perish (PoP) and VOS Viewer. Bibliometric analysis is a form of model that is carried out by exploiting research data that has been published online regarding the number of publications and authors of scientific publications. Publish or Perish (PoP) is a saying that describes the pressure to publish academic work in order to succeed in an academic career. Google Scholar, or commonly called Google Scholar, is a service provided by the technology giant Google which allows researchers around the world to search for learning materials in the form of text in various publication formats. The research results in this article examine the reality of drug crimes in the youth environment and analyze the policies that have been carried out by the government in an effort to handle these cases.